The first isolation of Trichosporon coremiiforme from soil in Iran - Samad Jamali; Majid Gharaei (Mazandaran University of Medical Sciences, 2015)
Background and Purpose: Trichosporon is a genus of anamorphic basidiomycetous yeast which is widely distributed in nature and is found in tropical and temperate areas. The aim of this work was to study the isolation, identification and molecular analysis of Trichosporon species in soil. Materials and Methods: In order to isolate and identify Trichosporon species in soil, 30 samples were collected from 30 different locations across Iran. The isolates were identified by means of the standard methods of yeast identification. To confirm morphological identification, genomic DNA was extracted and the hypervariable D1/D2 domain of the large-subunit (LSU) ribosomal DNA (rDNA) gene was amplified by polymerase chain reaction (PCR), using primer pair NL-1/NL-4, and then the sequences were analyzed. Results: According to the morphological and physiological assessments, isolates were identified as T. coremiiforme. The isolates formed chlamydospore after one week on yeast-malt (YM) agar medium. Using Blast program, we found that the D1/D2 sequences of the T. coremiiforme isolates from Iran (accession no: KP055040 and KP055041) showed 99% homology with the T. coremiiforme deposited in GenBank. All the T. coremiiforme isolates placed in the Ovoides cluster were well-supported by bootstrap values. Conclusion: The present study is the first attempt to survey Trichosporon in soil of Iran. To the best of our knowledge, this is the first investigation of T. coremiiforme in Iran.